The SLE-key test serological signature: new insights into the course of lupus. (4th June 2018) - Putterman, Chaim; Pisetsky, David S; Petri, Michelle; Caricchio, Roberto; Wu, Alan H B; Sanz, Ignacio; Oates, Jim C; Wallace, Steve; Sorek, Rachel; Gerwien, Robert; Safer, Pennina; Jakobi-Brook, Keren; et al.
Abstract: Objective: We previously described the multiplex autoantibody SLE-key Rule-Out test, which detects a signature of autoantibody reactivity that distinguishes healthy subjects from SLE patients with 94% sensitivity, 75% specificity and 93% negative predictive value; thus, an individual manifesting a positive Rule-Out test score is unlikely to have SLE (e.g. lupus is excluded). The objective of this current study was to evaluate the stability of the lupus-associated signature over time. Methods: We used banked serum samples from healthy subjects ( n = 51) and lupus patients ( n = 50 individual samples and n = 181 paired samples, for a total of n = 412 serum samples). The samples were drawn at different times after diagnosis to analyse the impact on the SLE-key Rule-Out test of time elapsed since diagnosis and any changes in disease activity (as reflected by the SLEDAI score). Results: The SLE signature remains stable for the first 10 years after diagnosis; in this time frame, <10% of patients manifested a positive Rule-Out score and the SLE-key Rule-Out score was independent of the underlying disease activity as reflected by the SLEDAI score. After ⩾10 years, ∼30% of lupus subjects scored as SLE Ruled-Out; the proportion of patients manifesting this status was even greater in the subset of individuals with a SLEDAI score of 0. Conclusion: These findings raise the possibility that a significant number of SLE patients manifest a change in their serological signature over time, and that such a signature change may signify an evolution in the immunological features of their disease relevant to patient management.